Penerapan Isometric Handgrip Exercise Pada Lansia Penderita Hipertensi Di RSUD dr. Soediran Mangun Sumarso Wonogiri - Fitri Shinta Muliya; Sri Hartutik; Agus Sutarto (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Background: Most hypertensive patients do not exhibit symptoms, although some symptoms occur unintentionally and are believed to be related to hypertension. This results in an increase in blood pressure with advancing age. Aging causes physiological changes in the body, such as the thickening of arterial walls due to the accumulation of collagen in the muscle layer, leading to the narrowing and stiffening of blood vessels starting at the age of 45 years. Objective: Aims to determine the results of implementing Isometric handgrip exercise in elderly hypertension patients. Method: A descriptive research design with a case study approach was conducted on two respondents. Results: Before the implementation of Isometric handgrip exercise, both respondents were at moderate risk of hypertension, however after performing the Isometric handgrip exercise with two contractions lasting 45 seconds each and a 15-second rest between the contractions, their blood pressure decreased. Conclusion: Isometric handgrip exercise shows a good influence on elderly hypertension patients.